Mechanical adherence analysis of polyurethane and polyester commercial coatings over alder wood - Chávez García, Dalia H.; Chanes González, Rubén; Guzmán, Mario (My University, 2021)
This study is the validation for a new method to introduce a new color coating in the fabrication of electric guitars, before this, the time for the validation was 20 to 25 days. This new validation reduced the time to 15 days and improved the time and quality process. The new method consisted in the mechanical adherence analysis of polyurethane and polyester commercial coatings. First, a database was generated to identify the type of material coating using FTIR technique with ATR. Also, the thermal expansion coefficients were measured to relate them to the adhesion. As a result, two methods of adhesion measurement were correlated, the quantitative pull-off method and the qualitative cross-cut method. Finally, a validation protocol was generated with the new tools.
Keywords: Polyurethane; Polyester; Coating; Painting; Adhesion; Campus Ensenada